The social costs of pesticide use in France - Alliot, Christophe; Mc Adams-Marin, Delphine; Borniotto, Diana; Baret, Philippe V. (Frontiers in Sustainable Food Systems, 2022)
The modern agricultural production system relies heavily on the use of synthetic pesticides, but over the course of recent decades various concerns have been raised on the associated negative externalities touching a variety of dimensions, such as human health and the environment. Yet, the magnitude of those effects is still unclear and data availability is scattered and heterogenous across dimensions, regions, and time. The public sector is called upon to develop and implement strategies to face those externalities and their associated social costs. This study aims to provide an assessment of social costs of pesticides in France in the prospect of an integration to the public budget spending, helping public authorities to identify financial flows of public funding with an impact perspective, within a methodological framework based on the social norms at the core of the public system. The results show that the social costs attributable to synthetic pesticide use in France amounted to 372 million euros, of which environmental costs are estimated at least at 291.5 million euros, health costs at least at 48.5 million euros, regulation at least at 31.9 million euros and public financial support to the sector at least at 0.4 million euros. For comparison, this total value of social costs represents more than 10% of the annual budget in 2017 of the French Ministry of Agriculture and Food (3 587 million euros). The analysis can be used as a monitoring indicator for the implementation of public policies in the context of the growing social and environmental issues they face.